Analysis of the public entrepreneurship phenomenon in a Brazilian state - Magnus Emmendoerfer; Josiel Lopes Valadares (Tourism & Management Studies)
This study examined the role of public entrepreneurs established in a state of Brazil. As our research showed, public entrepreneurs can be considered an innovation in people management in public service. An additional benefit that has improved this state’s public image and is a reference point for the rest of Brazil is how more objective criteria has been established in recruitment for positions of trust. However, the management model of public entrepreneurs presents significant challenges. It should be emphasised that competition with private companies is unequal because wages in the private sector are generally much higher than that of the public sector. The literature points to critical challenges in the promotion of entrepreneurship in the public sphere, revealing that there is the possibility that public entrepreneurship threatens democratic governance, promoting the self-interest of entrepreneurs.